Functional Adaptation of the Fibrocartilage and Bony Trabeculae at the Attachment Sites of the Anterior Cruciate Ligament. Issue 7 (2nd December 2019) - Suzuki, Daisuke; Otsubo, Hidenori; Adachi, Taiji; Suzuki, Tomoyuki; Nagoya, Satoshi; Yamashita, Toshihiko; Shino, Konsei
Abstract : The direct insertion of an enthesis is composed of uncalcified fibrocartilage (FC) and calcified FC, believed to function as buffers for multidirectional forces applied to the ligament. This study was performed to investigate the relationship between the FC thickness and bony trabecular orientation of the anterior cruciate ligament (ACL) on both the femoral and tibial sides. Six cadavers were examined (age at death: 73–92 years). Both femoral and tibial insertions of the ACL were harvested and used to make 0.5 mm interval semi‐serial sections. Microdigital images were taken and used to measure the maximum thickness of both the uncalcified FC and Calcified FC. Two‐dimensional discrete Fourier analysis was also performed to determine the orientation angle and orientation intensity of bony trabeculae directly under the FC. The mean thicknesses of the uncalcified FC at the femoral and tibial insertions were 0.98 mm and 0.49 mm, respectively. The mean thicknesses of the calcified FC were 0.47 mm and 0.38 mm, respectively. There was a significant difference in the uncalcified FC thickness, but not in the calcified FC thickness. The bony trabeculae showed a prominent orientation parallel to the ACL fiber on both sides, but it was more intense on the tibial side than on the femoral side. The trabecular orientation was prominent in the proximal‐posterior part of the femoral side and in the anteromedial part of the tibial side, suggesting that mechanical stress is greater in these parts. The dominant bony trabecular angle was 69.0° on the femoral side and 59.8° on the tibial side when the tidemark was set at 0°. These findings suggest that the femoral side receives multidirectional stresses, while relatively unidirectional stress is loaded on the tibial side. Furthermore, stress is considered to be greater in the proximal‐posterior part of the femoral insertion and in the anteromedial part of the tibial insertion. At the time of ACL reconstruction, attention should be paid to assign a robust portion of the graft to the posterior part of the femoral insertion and anteromedial part of the tibial insertion. Clin. Anat., 33:988–996, 2020. © 2019 Wiley Periodicals, Inc.